Problem Posing: Strategi yang Memfasilitasi Keterampilan Berpikir Tingkat Tinggi Matematika Siswa - Irna Karlina Sensiana Blegur (Universitas Nusa Cendana, 2022)
Higher Order Thinking Skills (HOTS) is one of the main goals in learning mathematics. Learning through problem solving is the key to developing this ability. Problem solving itself can be interpreted as an activity to solve complex problems which is problems that do not have automatic solutions but require reasoning to solve them. Generally, problems like these are given by the teacher during learning, then ask students to solve, with hope that students will learn and the development the HOTS during solving these problems. On the other hand, learning to solve problems can also be done using problems raised by the students themselves or known as problem posing. This strategy directs students to create new problems or reformulate problems based on the problems or information provided and then solve these new problems. This article aims to discuss problem posing strategy and examples of problem design using this strategy in integral calculus learning. Furthermore, how the problem posing strategy can facilitate students' mathematics HOTS during learning is also discussed in this article.